Adsorption Desulphurization of Gasoline by Silver Loaded onto Modified Activated Carbons - Bingcheng Cao; Wenzhong Shen; Yihong Liu (Adsorption Science & Technology)
The removal of organosulphur from gasoline by adsorption onto commercial carbon samples loaded with different amounts of silver nitrate was investigated. The pore structures of the samples were characterized by nitrogen adsorption studies, while the structure and chemical property of the samples before and after adsorption were examined and analyzed by XRD, FT-IR and SEM methods, respectively. The results showed that silver formed π-complexes with organic sulphides; the higher the silver loading, the greater the amount adsorbed. However, the adsorption selectivity was poor.